Challenges of Ukrainian Higher Education in Times of War - Ivanenko, Nadiya (International Higher Education, 2024)
Ukrainian higher education is facing unprecedented challenges due to Russia’s ongoing military invasion of Ukraine. Universities are striving to adapt to the new realities, maintaining their commitment to providing quality education while prioritizing safety of all the participants of the educational process. Educational losses get worse and have a negative impact on the country’s human capital and its economic well-being.